Effectiveness of Nutrition and Psychosocial Stimulation Modules on Knowledge, Attitude, and Abilities of Stunting Prevention Assistance - Sri Mulyanti; Yulia Lanti Retno Dewi; Eti Poncorini Pamungkasari (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
The prevalence of stunting in Indonesia until 2022 is still 24.4% (UNICEF Indonesia, 2022), still way below standard WHO is a maximum of 20% (WHO, 2018). Stunting is the failure of growth and development of children due to chronic lack of nutrition, recurrent infectious diseases, and inadequate psychosocial stimulation (WHO, 2018). Stunting causes barriers to cognitive development and the risk of metabolic disorders(Malhotra et al., 2014). Efforts to reduce stunting through community empowerment innovations need to be continuously developed, including the use of modules in assistant training to prevent stunting Quasy experiment research with pre post design to find out the effectiveness of the nutrition & psychosocial stimulation module on the knowledge, attitudes, and skills of assistants to prevent stunting. The research subjects were 30 assistants to prevent stunting, taken by purposive sampling. The research instruments are knowledge tests, attitude questionnaires, and skill checklists. Data were analyzed with the Dependent Paired T-Test. Media trainingThe Nutrition & Psychosocial Stimulation Module is effectiveincrease knowledge (p=0.00; mean: 82.50±9.45; CI: 95%), attitude towards giving complementary foods (p=0.000; mean: 76.87±9.76; CI: 95%), positive attitude towards giving psychosocial stimulation (p=0.000; mean: 72.66±7, 24; CI: 90%), and mentoring skills (p=0.000; mean: 77.93 ± 4.8; CI: 95%). Assistance Prevent Stunting Training (Pecis) using the Psychosocial Nutrition & Stimulation Module is effective for increasing knowledge, attitudes, and skills of Assistance for Preventing Stunting in providing assistance to mothers or caregivers of toddlers at risk of stunting.